2020
DOI: 10.1038/s41419-020-03260-9
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin prevents hyperglycemia-induced renal injuries by inhibiting inflammation and oxidative stress via SIRT1-dependent mechanism

Abstract: Diabetic nephropathy (DN) as a global health concern is closely related to inflammation and oxidation. Isoliquiritigenin (ISL), a natural flavonoid compound, has been demonstrated to inhibit inflammation in macrophages. Herein, we investigated the effect of ISL in protecting against the injury in STZ-induced type 1 DN and in high glucose-induced NRK-52E cells. In this study, it was revealed that the administration of ISL not only ameliorated renal fibrosis and apoptosis, but also induced the deterioration of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Renal SIRT1 is cytoprotective and is correlated to BP regulation and sodium balance ( Hao and Haase, 2010 ). Recent studies have focused on the role of SIRT1 in HN development and progression, primarily by protecting tubular cells from cellular stresses ( Guclu et al, 2016 ; Huang X. et al, 2020 ; Martinez-Arroyo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Renal SIRT1 is cytoprotective and is correlated to BP regulation and sodium balance ( Hao and Haase, 2010 ). Recent studies have focused on the role of SIRT1 in HN development and progression, primarily by protecting tubular cells from cellular stresses ( Guclu et al, 2016 ; Huang X. et al, 2020 ; Martinez-Arroyo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMPK also is found to be an important regulator participating in the macrophage phenotype [ 49 ]. SIRT1, a member of the SIRT family, has antiaging and anti-inflammatory effects [ 50 ]. SIRT1 acts as a downstream target of the AMPK pathway, and it also inhibits the activation of NF- κ B [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As is known to all, the anti-apoptosis ability of SIRT1 is self-evident [ 25 , 51 , 59 ]. Several studies showed that moderate SIRT1 overexpression could be effective in preventing drug induced apoptosis and oxidative stress [ 33 , 60 , 61 ]. In this study, the results suggested that up-regulation of SIRT1 induced by 17β-E2 inhibited apoptosis in hFOB1.19 osteoblasts.…”
Section: Discussionmentioning
confidence: 99%